Deciphering the role of TRIB1 in regulatory T-cells. (9th October 2015) - Danger, Richard; Dugast, Emilie; Braza, Faouzi; Conchon, Sophie; Brouard, Sophie
Abstract : The role of regulatory T-cells (Tregs) is crucial to maintain immune homoeostasis by controlling peripheral tolerance. A better understanding in the molecular mechanisms involved in the biology of these Tregs could improve their expansion and selection to treat immune-related diseases, achieve immunosuppression-free organ transplantation and to specifically target them in cancer. We reported on the overexpression of tribbles-1 (TRIB1) in Tregs compared with their counterpart naive T-cells and that TRIB1 interacts with the master molecule of Tregs, forkhead box P3 (FOXP3), a transcription factor essential for Treg suppressive activity. We demonstrated that these two molecules interact together in the nucleus of Tregs and TRIB1 overexpression is associated with a decrease in their proliferative capacities. Since TRIB1 was reported to be overexpressed in the blood of renal transplanted patients with chronic antibody-mediated rejection (CAMR), altogether, these results suggest TRIB1 could be linked to the decrease proportion of Tregs in patients exhibiting CAMR and a key player in Tregs through its FOXP3 interaction. In addition, yeast two-hybrid screening experiments highlighted that TRIB1 potentially interacts with molecules playing roles in intracellular events following T-cell activation and particularly cluster of differentiation (CD)4 + T-cells. This suggests still non explored potential links between TRIB1 in Tregs. Our goal is thus to decipher the role of TRIB1 in the Treg biology, notably in pathways known to involved its partner and main transcriptional factor of Tregs, FOXP3 and to determine the role of TRIB1 in immune pathologies.